2016
DOI: 10.1051/matecconf/20166703040
|View full text |Cite
|
Sign up to set email alerts
|

The Adsorption Mechanism of Modified Activated Carbon on Phenol

Abstract: Abstract. Modified activated carbon was prepared by thermal treatment at high temperature under nitrogen flow. The surface properties of the activated carbon were characterized by Boehm titration, BET and point of zero charge determination. The adsorption mechanism of phenol on modified activated carbon was explained and the adsorption capacity of modified activated carbon for phenol when compared to plain activated carbon was evaluated through the analysis of adsorption isotherms, thermodynamic and kinetic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
(34 reference statements)
0
12
0
1
Order By: Relevance
“…Lin et al, found that the pH of a solution close to pH pzc increases adsorption due to the fact that surface electrostatic interactions on activated carbon were zero, and phenol remained in molecular forms making π-π dispersion interaction stronger. A decrease in the pH leads to a more positive charge of the activated carbon surface, decreasing the adsorption capacity [20]. In this case, as compound's pH is far from pH pzc , electrostatic interactions does not seem to have an influence in the process.…”
Section: Understanding the Adsorption Mechanismmentioning
confidence: 95%
See 4 more Smart Citations
“…Lin et al, found that the pH of a solution close to pH pzc increases adsorption due to the fact that surface electrostatic interactions on activated carbon were zero, and phenol remained in molecular forms making π-π dispersion interaction stronger. A decrease in the pH leads to a more positive charge of the activated carbon surface, decreasing the adsorption capacity [20]. In this case, as compound's pH is far from pH pzc , electrostatic interactions does not seem to have an influence in the process.…”
Section: Understanding the Adsorption Mechanismmentioning
confidence: 95%
“…Some parameters are summarized in Table 1. The pH pzc of activated carbon was 10.08, from which it can be seen that for a pH lower than 10.08 the activated carbon surface has a positive charge and if the pH is higher the surface charge is negative [20]. These results are compared with the solution and solute properties in order to provide some explanations about the adsorption mechanisms.…”
Section: Adsorbent Characterizationmentioning
confidence: 99%
See 3 more Smart Citations